Cross-country differences in monetary policy transmission - Robert-Paul Berben; Alberto Locarno; Julian Morgan; Javier Vallés (European Central Bank (ECB), 2004)
This paper examines possible explanations for observed differences in the transmission of euro area monetary policy in central bank large-scale macroeconomic models. In particular it considers the extent to which these differences are due to differences in the underlying economies or (possibly unrelated) differences in the modelling strategies adopted for each country. It finds that, against most yardsticks, the cross-country variations in the results are found to be plausible in the sense that they correspond with other evidence or observed characteristics of the economies in question. Nevertheless, the role of differing modelling strategies may also play a role. Important features of the models - for instance in the treatment of expectations or wealth - can have a major bearing on the results that may not necessarily reflect differences in the underlying economies.
Keywords: C53; E52; E37; 330; euro area differences; macroeconometric models; monetary transmission